Voters in the face of election mechanism and scope of leaders authority in Polish political parties - Tomczak, Łukasz (Political Preferences, 2013)
The article refers to the ratio of voters to choose the method and scope of leaders authority in the Polish political parties such as the Law and Justice party, Civic Platform, Polish Peasant Party, Palikot's Movement and the Democratic Left Alliance (SLD). Most party leaders are elected by indirect suffrage. From the test batches only the leader of SLD had been once directly selected. The majority of respondents (both left-wing, right-wing and centrist) supported the idea of direct selection. However more often, a direct dial is in favor of left-wing voters. The scope of formal power increases with the leaders of the party from the left to the right point of the political spectrum. The subjects were different approach to the scope of authority of leaders. More left-wing voters were in favor of limiting their rights, right-wing supporters were often in favor of making authority leaders stronger. Internal regulations of the studied formations correspond to the expectations of voters as to the extent of its formal powers. However, differ as to the expected pattern of choice.